Funding Amounts of Free Day Secondary Education and Student Retention: A case of Migori County, Kenya - Achieng, Madeleine Sophie Barat; Elizabeth Nduku; Harriet Njui (IJRDO- Journal of Educational Research, 2021)
Funding of secondary education according to European Commission (2014) is the focus of much debate in Europe today. This has challenged decision makers and educationists all over Europe to seek new ways of ensuring that sufficient funds are made available for schools while using public resources efficiently. Most developing countries also face great challenges associated with funding of secondary education. In Kenya, free day secondary education was introduced in 2008 to enhance transition and retention of students from primary to secondary schools. Studies have shown that student retention is still a major challenge among the vulnerable and marginalized students. The government of Kenya has continued to explore different ways of financing education in order to improve quality and expand secondary education. This study was anchored on retention theory and sought to add knowledge and literature related to funding of secondary education and student retention. The sample of the study consisted of 19 schools, 228 students, 76 class teachers, 31 parents, 19 school principals and 1 Quality Assurance and Standards Officer. The study adopted a convergent parallel mixed method research design using a cross sectional survey design for the quantitative method and a case study design for the qualitative method. Data were collected using questionnaires, interview guides, document analysis guide and focus group discussions. Descriptive and inferential statistics were generated using MS Excel 2018 and SPSS version 21. Qualitative data from the interviews and focus group discussions were analysed thematically and report given in narrative form and direct quotes. The findings revealed that free day secondary education funding had contributed to the improvement of student retention in Migori County over the last four years. The study recommended that the government should review the amounts allocated for free day secondary education and consider investment in education a key priority.